Readings in sexualities from Africa - Spronk, Rachel; Hendriks, Thomas (Readings in African studies., 2020)
Images and stories about African sexuality abound in today's globalized media. Frequently old stereotypes and popular opinion inform these stories, and sex in the media is predominately approached as a problem in need of solutions and intervention. The authors gathered here refuse an easy characterization of African sexuality and instead seek to understand the various erotic realities, sexual practices, and gendered changes taking place across the continent. They present a nuanced and comprehensive overview of the field of sex and sexuality in Africa to serve as a guide though the quickly expanding literature. This collection offers a set of texts that use sexuality as a prism for studying how communities coalesce against the canvas of larger political and economic contexts and how personal lives evolve therein. Scholars working in Africa, the U.S., and Europe reflect on issues of representation, health and bio-politics, same-sex relationships and identity, transactional economies of sex, religion and tradition, and the importance of pleasure and agency. This multidimensional reader provides a comprehensive view of sexuality from an African perspective.